Usefulness of disposable skin biopsy punch for cervical occlusion after cervical conization - Rina Funada; Kazushige Adachi; Yoshimitsu Yamamoto; Itsuko Nakamichi (Wolters Kluwer Medknow Publications, 2020)
Cervical occlusion is a rare but serious complication after conization of the uterine cervix. We report on a 69-year-old woman with cervical intraepithelial neoplasia (CIN) 2, who successfully underwent follow-up biopsy of an occluded cervical canal after conization using a disposable skin biopsy punch. The disposable skin biopsy punch was inserted into a slight dimple, which was considered a uterine os, in the direction of the cervical canal, and a sample of tissue was obtained from the occluded portion. This procedure was performed without anesthesia and was completed uneventfully. Histological examination of the excised tissue revealed CIN 3. In addition, the procedure resulted in recanalization of the occluded cervical canal. The occlusion was limited in the external portion of the cervical os and attributed to adhesion of scar tissue during the healing process. Our experience suggests that a disposable skin biopsy punch can be used for follow-up biopsy and recanalization in patients with cervical occlusion after conization as a less invasive approach.